Sokerijuurikkaan harvennustyön tutkimusmenetelmästä - Sipilä, Martti (Agricultural and Food Science, 1955)
In carrying out a time study in the field of agricultural work it is very rarely that situations occur in which the outward conditions which affect the work could be regarded as completely invariable and in which the time spent on the work would be the only varying factor to be recorded. On the contrary, most often quite a number of different factors have an effect on the carrying out of the work, so many factors, indeed, that only the most important of them can be taken into account when carrying out time study. Almost without exception, therefore, a preliminary study must be made first, its aim being to clear up the most important of the factors affecting the work and to determine which of them should be taken into account in the final study. Furthermore, the preliminary study determins the measurement of the affecting factors either with objective measuring methods or by creating a classification, based on a subjective estimate made by a time study engineer, which can be considered sufficiently clear and practicable. In the study now in hand the thinning of sugar-beet with a shortshafted hoe, using the pull push method a preliminary study has been made of the work performed by several men on one day. On the basis of the preliminary study the following factors affecting the work were finally chosen to be included: the average length of the seedlings, the quality of the surface of the soil, abundance of weeds in the soil, and the number of the seedlings left at the thinning. As the unit used in the study the work done on 10 linear metres was chosen, and the determination of the different factors was correspondingly fixed. For the estimation of the abundance of weeds in the soil the following classification was made: I Class no weeds II » weeds in places III » some weeds IV » a moderate number of weeds V » weeds in abundance The quality of the surface of the soil was divided into three classes: I Class loose II » clods, somewhat encrusted III » clods, very encrusted, the soil hard. Furthermore, special instructions were given in regard to both of the aforementioned classifications, and their application was made uniform by the group training of the persons collecting the material. The length of the seedlings was measured by taking samples from three points on the unit under observation, and the mean average was computed. The number of the seedlings left at the thinning was taken from each research unit as the sum total. For the mathematical treatment of the material, the different factors were given symbols as follows: x1 = time spent on work/10 linear metres x2 = average length of seedlings/10 linear metres x3 = quality of surface of soil/10 linear metres x4 = abundance of weeds in soil/10 linear metres x5 = number of seedlings left at thinning/10 linear metres The statistically-mathematical treatment of the material is based on the hypothesis, reached on the basis of a preliminary study, that the time x1 is linearly dependent on the factors x2, x3, x4 and x5 which affect the work. The phenomenon may be described by a straight line the equation of which has the form: x1 = a + b * x2 + c * x3 + d * x4 + e * x5 and shows the simultaneous variation of the different arguments which affect the work. On the basis of the characteristics computed from the primary material the estimated final value of the aforementioned regression line of the work is: x1 = 0.15 + 0.05 * x2 + 0.40 * x3 + 0.47 * x4 + 0.05 * x5. To allow comparison the mathematical treatment was carried out, also by using a partial correlation computation. The coefficients of the correlation series are shown on page 224. In the series of the final coefficients of correlation r12x345 = 0.10 r13x245 = 0.33 r14x235 = 0.63 r15x234 = 0.35 the significance of the value r12x315 = 0.10 is so small that it cannot be regarded as probable. The other values, on the other hand, describe the phenomenon with an accuracy probability of 95%. To check the mathematical treatment on the basis of the aforementioned coefficients of correlation, the values of the coefficients a, b, c, d and e in the equation x1 = a + bx2 + cx3 + dx4 + ex5 have been computed and a result has been arrived at which is completely consistent with the result reached by the computation of the regression line. For practical application, working time values/10 linear metres, which are in accordance with the straight line obtained, have been computed on to Table No. 1, page 225. Also the additional 7.5 % have been taken into consideration in the calculations as corresponding to accepted interruptions, in accordance with the preliminary study. Since the importance of the lenght of the seedlings is of very little significance and not even probable, it has not been taken into consideration. The computations have been made as corresponding to a length of 5 cm. of the seedlings. Table No. 1 shows the money values which are in accordance with the time values on Table No. 1 and which keep to the basis agreed upon at the negotiations between the organizations on the labour-market. As the work in question has been work on a contract a 30 % increase for the contract has been agreed upon to be observed. Table No. 2 has been computed according to wages of 80 mks. per hour and the prices have been stated in pennies as the price paid for work per metre. The increase corresponding to the contract has been allowed in the figures.